2023
DOI: 10.55908/sdgs.v11i4.893
|View full text |Cite
|
Sign up to set email alerts
|

Financial Ratios, Corporate Governance, and Macroeconomic Indicators in Predicting Financial Distress

Dwivinna Nadine Dewi,
Werner Ria Murhadi,
Bertha Silvia Sutejo

Abstract: Purpose: This study analyzed the effect of financial ratios, corporate governance, and macroeconomic variables on financial distress. This research was conducted during the covid-19 pandemic when many companies experienced difficulties due to activity restrictions during the pandemic.   Theoretical framework: Prolonged financial difficulty can lead to the company's insolvency. As a result, understanding the company's health status is critical. Internal company factors, such as the firm's financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…The second is social, and it deals with how the company interacts with its customers, employees, and community members, as well as its commitment to diversity, fighting corruption, and upholding human rights all throughout the supply chain. The final element is governance, which has t o do with balancing shareholder and stakeholder interests and adhering to GCG (Dewi, Murhadi, & Sutejo, 2023). The ability of a business to utilize natural resources effectively and lower environmental emissions is referred to as the environmental dimension.…”
Section: Environmental Social and Governancementioning
confidence: 99%
“…The second is social, and it deals with how the company interacts with its customers, employees, and community members, as well as its commitment to diversity, fighting corruption, and upholding human rights all throughout the supply chain. The final element is governance, which has t o do with balancing shareholder and stakeholder interests and adhering to GCG (Dewi, Murhadi, & Sutejo, 2023). The ability of a business to utilize natural resources effectively and lower environmental emissions is referred to as the environmental dimension.…”
Section: Environmental Social and Governancementioning
confidence: 99%
“…This study is based on the concept of a valuation model, which explains that the asset value is the proxy of the expected return on present value for the asset holding of investors. The variation of asset value is probably influenced by many factors which may have an effect on the expected return, such as business performance, economic factors, the situation of each industry as the result of Dewi et al (2023) investors which found that the financial ratios, governance and macroeconomic indicators can be used as a investors possibility of financial distress because the investor usually use news to help the choosing investment and financial planning (Murhadi et al, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%